Direct And Indirect Influence Of Career Development And Human Resource Development On Professionality And Its Impact On Personnel Performance At The Jambi Polda Human Resources Bureau - Bukit, Pantun; Akbar, Ali; Pane, Leny Kasari (International Journal of Advanced Multidisciplinary, 2024)
This research aims to determine and analyze the direct and indirect influence of career coaching and human resource development on professionalism and its impact on personnel performance at the Jambi Regional Police Human Resources Bureau. This is because human resources must receive career coaching and development so as to increase professionalism to encourage increased employee performance. The literature review in this research uses reference sources based on the variables used, namely career coaching, human resource development, professionalism and personnel performance. Where, each variable will be explained definitively, examining dimensions and indicators, as well as the relationship between the variables themselves. The research was conducted using descriptive analysis methods to determine the scale and quantitative analysis (path analysis) based on the research variables used. The research object itself is the Jambi Regional Police Human Resources Bureau with a population and sample of 62 personnel. The research results show that: 1) The total score for the Career Development (X1) and Human Resources Development (X2) variables is in the good category, while the Professionalism (Y) and Personnel Performance (Z) variables are in the High category; 2) The Career Development variable (X1) directly 11.16% and indirectly 17.16% and Human Resources Development (X2) has a direct influence of 23.33% and indirectly 51.65% on Professionalism (Y); 3) The Career Development variable is directly .92% and indirectly 13.98% (X1) and HR Development directly 25% and indirectly 45.9% (X2) has a direct influence on Personnel Performance (Z); 4) The Professionalism Variable (Y) has a direct influence of 33.76% and other factors 66.24% on Personnel Performance (Z); and 5) Career Development (X1), HR Development (X2), and Professionalism (Y) variables have a positive and significant influence on Personnel Performance (Z). Thus, career coaching and human resource development directly and indirectly through professionalism on the performance of personnel at the Jambi Regional Police Human Resources Bureau has a positive and significant effect.